Drunken Speech: The Impact of Dialect and Alcohol Intoxication on Mock Juror Perceptions of Sexual Assault Victims - Gawrylowicz, Julie; Kirk, Neil W. (Applied cognitive psychology, 2025)
ABSTRACT This study explored how alcohol intoxication and dialect influence mock jurors' perceptions of a sexual assault victim's credibility, blameworthiness, consent, verdicts and sentence length. A 2 × 2 between‐subjects design involved 198 participants (recruited from the community and university campus) who read a fictional trial vignette, with the victim portrayed as either intoxicated or sober. Thereafter, they listened to an emergency call recorded by a bidialectal speaker, with the victim speaking either Scottish Standard English or the non‐standard Dundonian dialect. Although victims speaking Dundonian were perceived as less credible, dialect did not influence verdicts or sentencing decisions. Contrary to previous research, the victim's intoxication status did not affect mock jurors' decision‐making. These findings highlight the importance of addressing linguistic biases to ensure fair trial outcomes.